SEROPREVALENCE OF CHLAMYDIA PNEUMONIAE ANTIBODIES AMONG CHILDREN ADMITTED FOR RESPIRATORY INFECTIONS IN SULAIMANI PEDIATRIC TEACHING HOSPITAL - Abdulrahman, Alan Abdula; Hussain, Ali Hattem; Othman, Nasih; Gubari, Mohammed Ibrahim M. (Journal of Sulaimani Medical College, 2015)
Background The incidence of severe acute respiratory tract infections in children caused by Chlamydia pneumoniae varies greatly from year to year and place to place around the world. Chlamydia pneumoniae, a bacterium that causes respiratory infections, is probably under-diagnosed, it’s of worldwide distribution. The seroprevalence of C. pneumoniae antibody is age dependent. Objectives This study examined the prevalence of C. pneumoniae infections, their clinical manifestations and demographic features in hospitalized children with respiratory tract infections. The study also tested two different immunological techniques for detection C. pneumoniae infections. Methods This cross sectional study was carried out in Sulaimani Pediatric teaching hospital. One hundred and twenty seven children aged less than 5 years, hospitalized for respiratory tract infections were enrolled in this study. Serum anti-C. pneumoniae specific IgM and IgG antibodies were measured using an enzyme-linked immunosorbent assay (ELISA) and indirect immunofluorescent assay technique (IFA). The clinical and demographic data were compared between positive C. pneumoniae antibodies and negative C. pneumoniae antibodies. Results Acute C. pneumoniae infections were detected using IgM anti-C. pneumoniae antibodies which were positive in 5 (3.9%) children by ELISA technique and the same result was obtained by IFA technique. IgG anti-C. pneumoniae antibodies were positive in 32 (25.2%) and 33 (25.9%) by ELISA and IFA respectively, the results of the two tests were similar and the differences were statistically not significant. Clinical and demographic data of patients with C. pneumoniae infections were comparable to those of negative IgM anti-C. pneumoniae antibodies. Conclusion C. pneumoniae has a role in children hospitalization with respiratory tract infections in Sulaimani Governorate. ELISA technique is a good alternative for IFA in serological diagnosis of C. pneumoniae infections.
Keywords: Hospitalized children; Anti-Chlamydia pneumoniae antibodies; ELISA technique; IFA technique; respiratory tract infections